2005
DOI: 10.1016/j.micres.2005.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of homologues to the pathogenicity factor Pat-1, a putative serine protease of Clavibacter michiganensis subsp. michiganensis

Abstract: Hybridization of Clavibacter michiganensis subsp. michiganensis total DNA against the pathogenicity gene pat-1 indicated the presence of pat-1 homologous nucleotide sequences on the chromosome and on plasmid pCM2. Isolation of the corresponding DNA fragments and nucleotide sequence determination showed that there are three pat-1 homologous genes: chpA (chromosome) and phpA and phpB (plasmid pCM2). The gene products share common characteristics, i.e. a signal sequence for Sec-dependent secretion, a serine prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…michiganensis is the occurrence of numerous genes encoding extracellular proteases, although when C. michiganensis subsp. michiganensis is grown on agar plates containing casein or skim milk, it shows no proteolytic activity (9). At least 28 serine proteases belonging to three different families were identified.…”
Section: Michiganensismentioning
confidence: 99%
See 3 more Smart Citations
“…michiganensis is the occurrence of numerous genes encoding extracellular proteases, although when C. michiganensis subsp. michiganensis is grown on agar plates containing casein or skim milk, it shows no proteolytic activity (9). At least 28 serine proteases belonging to three different families were identified.…”
Section: Michiganensismentioning
confidence: 99%
“…The plasmid-encoded Pat-1 was shown to be necessary for symptom development (wilting), but not for colonization of the tomato plant (13). Analysis of a mutant in which the serine in the catalytic triad was replaced by a threonine via site-specific mutagenesis suggested that pat-1 probably encodes a functional serine protease (9). The other genes in pCM2, phpA and phpB, are not essential for pathogenicity because the plasmid-free strain CMM100 colonizes normally and cloning of these genes into CMM100 did not affect the nonvirulent phenotype of the strain (9,40).…”
Section: Michiganensismentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, these advances allowed breakthrough identification of a novel set of pathogenicity-related genes in the tomato pathogen Clavibacter michiganensis subsp. michiganensis and identification of homologues in other coryneform plant pathogens (15,27,32; see the accompanying paper). Because methodologies created for functional analysis of C. michiganensis subsp.…”
mentioning
confidence: 99%